2021
DOI: 10.3390/vaccines9080939
|View full text |Cite
|
Sign up to set email alerts
|

Nervous and Muscular Adverse Events after COVID-19 Vaccination: A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: Background: Nervous and muscular adverse events (NMAEs) have garnered considerable attention after the vaccination against coronavirus disease (COVID-19). However, the incidences of NMAEs remain unclear. We aimed to calculate the pooled event rate of NMAEs after COVID-19 vaccination. Methods: A systematic review and meta-analysis of clinical trials on the incidences of NMAEs after COVID-19 vaccination was conducted. The PubMed, Medline, Embase, Cochrane Library, and Chinese National Knowledge Infrastructure da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…With the starting vaccination, several studies were carried out to ascertain the safety of these vaccines, since they were produced in record time. 20–22 Currently, one systematic review about the thematic showed that of 11 published clinical trials of COVID-19 vaccines included in the study, adverse reactions reported were considered mild to moderate with few severe reactions which were unrelated to the test vaccine. Common adverse events were pain at the site of injection, fever, myalgia, fatigue and headache.…”
Section: Discussionmentioning
confidence: 99%
“…With the starting vaccination, several studies were carried out to ascertain the safety of these vaccines, since they were produced in record time. 20–22 Currently, one systematic review about the thematic showed that of 11 published clinical trials of COVID-19 vaccines included in the study, adverse reactions reported were considered mild to moderate with few severe reactions which were unrelated to the test vaccine. Common adverse events were pain at the site of injection, fever, myalgia, fatigue and headache.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of NMAEs was 29.2% in the vaccine group and 21.6% in the control group, in a total of 15 randomized blinded controlled clinical trials. Systemic neurological symptoms included migraine, dizziness, vertigo, and syncope ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tsun-Haw Toh MRCP 1 Yen-Fa Toh MPath 2 Kum-Thong Wong FRCPath 2 Nortina Shahrizaila FRCP 1 Khean-Jin Goh FRCP 1 1…”
Section: Cheng-yin Tan Mmedmentioning
confidence: 99%
“…We read with great interest the study of Pham Nguyen et al on the potential of macrolides and fluoroquinolones to worsen myasthenia. 1 We were surprised by the low and insignificant odds ratios (ORs) for myasthenia worsening for fluoroquinolones and macrolides in comparison to beta lactam antibiotics. This is in contrast to a recent result from pharmacovigilance data from the World Health Organization (WHO)…”
Section: The Difficulty Of Confirming Pharmacovigilance Signals In My...mentioning
confidence: 99%
See 1 more Smart Citation